Spraying exogenous hormones alleviate impact of weak-light on yield by improving leaf carbon and nitrogen metabolism in fresh waxy maize - Li, Guanghao; Li, Wei; Liang, Yuwen; Lu, Weiping; Lu, Dalei (Frontiers in Plant Science, 2023)
Insufficient light during the growth periods has become one of the main factors restricting maize yield with global climate change. Exogenous hormones application is a feasible measure to alleviate abiotic stresses on crop productivity. In this study, a field trial was conducted to investigate the effects of spraying exogenous hormones on yield, dry matter (DM) and nitrogen (N) accumulation, leaf carbon and N metabolism of fresh waxy maize under weak-light stress in 2021 and 2022. Five treatments including natural light (CK), weak-light after pollination (Z), spraying water (ZP1), exogenous Phytase Q9 (ZP2) and 6-benzyladenine (ZP3) under weak-light after pollination were set up using two hybrids suyunuo5 (SYN5) and jingkenuo2000 (JKN2000). Results showed that weak-light stress significantly reduced the average fresh ear yield (49.8%), fresh grain yield (47.9%), DM (53.3%) and N accumulation (59.9%), and increased grain moisture content. The net photosynthetic rate (Pn), transpiration rate (Tr) of ear leaf after pollination decreased under Z. Furthermore, weak-light decreased the activities of RuBPCase and PEPCase, nitrate reductase (NR), glutamine synthetase (GS), glutamate synthase (GOGAT), superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in ear leaves, and increased malondialdehyde (MDA) accumulation. And the decrease was greater on JKN2000. While ZP2 and ZP3 treatments increased the fresh ear yield (17.8%, 25.3%), fresh grain yield (17.2%, 29.5%), DM (35.8%, 44.6%) and N (42.5%, 52.4%) accumulation, and decreased grain moisture content compared with Z. The Pn, Tr increased under ZP2 and ZP3. Moreover, the ZP2 and ZP3 treatments improved the activities of RuBPCase, PEPCase; NR, GS, GOGAT; SOD, CAT, POD in ear leaves, and decreased MDA content during grain filling stage. The results also showed the mitigative effect of ZP3 was greater than ZP2, and the improvement effect was more significant on JKN2000.